Analisa Kapasitas Tingkat Pelayanan Lalu Lintas Tanpa Signal pada Persimpangan Jalan Tirto Utomo Tlogomas Landungsari. - Ceu, Albino Maia Do; Pandulu, Galih Damar; Arifianto, Andy Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2018)
ABSTRACT Malang is the second major city after the city of Surabaya in East Java with tourist potential and its economy is growing. The activities such as malls, markets, parks, campuses, tourist areas, office activities and other activities are factors that make this street has a solid activity that resulted in the problem - the problem of transport one road congestion resulting in decreased capacity, In the survey or the study used data collection methods with Manual Method Counter at the crossroads Tirto Utomo Tlogomas Landungsari Malang with the purpose of calculating the value of traffic volume, capacity and level of service is to conduct a survey for 14 days (starting from 6:00 pm - 22:00 WIB) and survey data obtained vehicle traffic volume and road geometric data are then analyzed using the Indonesian Highway Capacity Manual (MKJI) 1997. Based on the analysis, the volume of peak hour at a crossroads Tirto Utomo Tlogomas Landungsari was 9256 smp / hour, ), capacity of 3206.82 and the level of service (LOS) is F. Keywords: capacity, analysis of traffic services.